A season of perfect happiness : a novel - Fischer, Maribeth ([New York, New York] : Dutton, 2024)
"Ten years after an unspeakable tragedy caused Claire to flee her hometown in Delaware, she finally feels content. She has a quiet, tidy life in Wisconsin, a place she picked at random for its perfect pink mitten shape on a map. Her carefully constructed identity is predicated on a simple plan: keep her social circle small, and keep the past a secret. But when she meets Erik--a lighthearted theater nerd who gives Claire more of a chance than she's given herself in a long time--that plan seems increasingly impossible, especially after she finds herself emotionally entangled not only with Erik, but with his ex-wife Annabelle, their three young children, and a small set of friends, the kind she'd always wanted to have around her"--
Keywords: Secrecy -- Fiction; Friendship -- Fiction; Families -- Fiction; Self-actualization (Psychology) in women; Wisconsin -- Fiction; Domestic fiction